2001
DOI: 10.1177/1532673x01293002
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation Delay for Vacancies on the Circuit Courts of Appeals

Abstract: Supreme Court confirmation is an exhaustively studied phenomenon, but lower court confirmation is less well understood, in part because lower court nominees are very rarely rejected, and the Senate fails even to hold a recorded vote for most appointees. However, the length of time it takes to fill a judicial vacancy serves as alternate evidence of conflict between the president and the Senate. We present an empirical assessment of appellate vacancy conflict, based on a continuous time-proportional hazard model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…In addition to the political context surrounding the confirmation process, previous studies have found a relationship between confirmation delay and the presidential election cycle, with nominations made later in a presidential term experiencing more delay than those referred earlier (Martinek et al 2002;Nixon and Goss 2001;Solowiej et al 2005). Furthermore, Martinek et al (2002) found that judicial nominees were treated less favorably when referred in a president's second term.…”
Section: The Timing Of the Nominationmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition to the political context surrounding the confirmation process, previous studies have found a relationship between confirmation delay and the presidential election cycle, with nominations made later in a presidential term experiencing more delay than those referred earlier (Martinek et al 2002;Nixon and Goss 2001;Solowiej et al 2005). Furthermore, Martinek et al (2002) found that judicial nominees were treated less favorably when referred in a president's second term.…”
Section: The Timing Of the Nominationmentioning
confidence: 98%
“…These studies have included consideration of divided government (Bell 2002b;Binder and Maltzman 2002;Scherer et al 2008;Sollenberger 2010), the size of the opposing party's delegation in the Senate (Nixon and Goss 2001), the ideological distance between the president and a key member of the Senate (Basinger and Mak 2010;Binder andMaltzman 2002, 2009;Primo et al 2008;Scherer et al 2008), and the proportion of opposing-party members on the Judiciary Committee (Martinek et al 2002). Previous descriptive analyses have found that most of the delay seen in the modern confirmation process occurs at the committee stage (Goldman 2003;Goldman et al 2011;Slotnick and Goldman 1998), and that the Judiciary Committee chair is particularly important in determining the extent of delay imposed by the committee (Scherer 2005).…”
Section: Political Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Federal judicial appointments are less likely to be confirmed during a president's second term (Hagle, 1993;Nixon & Goss, 2001;Spriggs & Wahlbeck, 1995), and FCC vacancies persisted longer during second presidential terms (Nixon, 2001). A dummy variable for whether a vacancy arose during a president's second term has been included to determine if this phenomenon is present at the NTSB.…”
Section: Modelmentioning
confidence: 99%